Sosialisasi Website Sekolah sebagai Identitas Digital Sekolah Pada PAUD–TK IGABA - Edy Anan; Ahmad Sa’di; Yola Andesta Valenty (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
The main issue addressed in this community service activity is the low adoption of official school websites using the .sch.id domain among PAUD–TK IGABA schools, resulting in weak digital identity and limited public access to information. This program aims to improve school administrators’ understanding and technical skills in utilizing websites as a medium for institutional digital identity. The methods employed include dissemination, interactive seminars, discussions, and basic website management practices supported by guidance modules. The results indicate a significant increase in participants’ understanding of the strategic role of school websites and the importance of the .sch.id domain, as well as improvements in basic technical skills for website creation and content management. Additionally, participants showed increased motivation to develop official school websites, evidenced by follow-up actions and requests for assistance. This activity effectively enhances schools’ digital readiness and supports sustainable digital transformation in education.